2005
DOI: 10.1080/14639230400028455
|View full text |Cite
|
Sign up to set email alerts
|

A knowledge audit of the managers of primary care organizations: top priority is how to use routinely collected clinical data for quality improvement

Abstract: Technology has provided improved access to the rapidly expanding evidence base and to computerized clinical data recorded as part of routine care. A knowledge audit identifies from within this mass of information the knowledge requirements of a professional group or organization, enabling implementation of an appropriately tailored knowledge-management strategy. The objective of the study is to describe perceived knowledge gaps and recommend an appropriate knowledge-management strategy for primary care. The sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Additionally, it involves acquiring, tracking, evaluating and maintaining knowledge (Ash et al ., ). A broad rather than a narrow approach to KM in healthcare is preferable, and learning strategies are vital if quality‐improvement targets are to be reached (De Lusignan et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, it involves acquiring, tracking, evaluating and maintaining knowledge (Ash et al ., ). A broad rather than a narrow approach to KM in healthcare is preferable, and learning strategies are vital if quality‐improvement targets are to be reached (De Lusignan et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…The amount and quality of information is frequently questionable. Sometimes, information is precise or adequate (De Lusignan et al ., ), and others, there is too much information. Decision makers indicated that they are overwhelmed with the effort to assimilate the received information (Dobbins et al ., , p.125):
‘There is so much information sent to you that most of us are completely bogged down by what's in our inboxes.
…”
Section: Resultsmentioning
confidence: 99%
“…To improve quality of care, patient safety and decrease care variation, evidenced based practices are required ( De Lusignan, Wells, Shaw, Rowlands, & Crilly, 2005 ). After reviewing the current initiatives of optimizing the quality of care and patient safety, the following are the main implications and lessons learned which could help researchers, policy makers, leaders, care organizations and providers to sustain the performance of delivering best practices:…”
Section: Discussionmentioning
confidence: 99%
“…Though, much of what has been done till now in E.H.R. involves data processing mainly (Van Vlymen, De Lusignan, Hague, Chan, & Dzregah, 2005); besides, health service managers are facing many difficulties when tying to access relevant data routinely for quality improvement (De Lusignan, Wells, Shaw, Rowlands, & Crilly, 2005). KM techniques can play here two roles one for managers and one for practitioners; indeed, KM techniques can help in searching for knowledge in the mass of data gathered helping practitioners to find more effective ways to treat patients by searching for similar patient case histories (O'Sullivan, et al, 2007), and helping managers to get relevant knowledge for total quality management (TQM) (McAdam & Leonard, 2001).…”
Section: Electronic Health Record (Ehr)mentioning
confidence: 99%